Gender Equality in Islamic Sharia (The Study of Bisri Mustofa's Thought in Al-Ibrīz li Ma'rifah Tafsīr Al-Qur'ān Al-'Azīz) - Achmad Mudhofar 'Afif; Maskur Rosyid; Lutfi Lutfi (Syariah: Jurnal Hukum dan Pemikiran, 2022)
Abstract: The problem of gender inequality is a significant concern in the dynamics of Islamic law. The meaning of the verses of the Qur'an in this matter is strongly influenced by the social constructs surrounding it. This article aims to find Bisri Mustofa's thoughts in Al-Ibrīz li Ma'rifah Tafsīr al-Qur'ān al-'Azīz about verses with the theme of gender and women. This paper uses a descriptive qualitative method. The data collected were analyzed using the theory of hermeneutic philosophy and the theory of gender equality by Mansour Fakih. This article finds that Bisri Mustofa's interpretation tends to be gender-biased due to the Javanese culture surrounding it.Keyword: gender; tafsīr; al-Ibrīz; Javanese culture Abstrak: Problem ketimpangan gender menjadi perhatian utama dalam dinamika pensyariatan Islam. Pemaknaan ayat-ayat al-Qur'an dalam masalah tersebut sangat dipengaruhi oleh konstruk sosial yang mengitarinya. Artikel ini bertujuan untuk menemukan pemikiran Bisri Mustofa dalam kitabnya yang berjudul Al-Ibrīz li Ma'rifah Tafsīr al-Qur'ān al-'Azīz tentang ayat-ayat Al-Qur'an dengan tema gender dan perempuan. Tulisan ini menggunakan metode deskriptif-kualitatif. Data yang terkumpul dianalisis menggunakan dua teori; teori filsafat hermeneutika, dan teori kesetaraan gender Mansour Fakih. Arikel ini menemukan bahwa penafsiran Bisri Mustofa cenderung bias gender. Kecenderungan ini disebabkan oleh budaya Jawa yang melingkupinya.